2005
DOI: 10.1007/s00345-004-0490-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and partner-related factors in rapid ejaculation: Differences between dysfunctional and functional men.

Abstract: Despite the high prevalence of rapid ejaculation in community samples, there is still a paucity of data on cognitive and other relevant aspects of the subjective experience of premature ejaculation (PE) patients and their functional counterparts. Therefore, the main aim of this study was to expand our understanding of the complex nature of rapid ejaculation disorders by providing a detailed characterization of ejaculatory patterns, behavioral aspects, cognitive, and partner-related factors in a sample of unsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 9 publications
1
102
0
4
Order By: Relevance
“…Specifically, some authors have demonstrated the negative impact of cognitive factors on ejaculation and orgasmic pleasure. Among these, the most frequent negative thoughts include preoccupation about controlling the orgasm, anticipation of a possible failure, distracting thoughts and thoughts about keeping the erection, concentration about satisfying the partner rather than himself (Hartmann et al, 2005). One may infer that a man not distressed by his prematurity regarding ejaculation does not perceive a reduced orgasmic intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, some authors have demonstrated the negative impact of cognitive factors on ejaculation and orgasmic pleasure. Among these, the most frequent negative thoughts include preoccupation about controlling the orgasm, anticipation of a possible failure, distracting thoughts and thoughts about keeping the erection, concentration about satisfying the partner rather than himself (Hartmann et al, 2005). One may infer that a man not distressed by his prematurity regarding ejaculation does not perceive a reduced orgasmic intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported for PE, a largely recognized partner-oriented male sexual symptom. Indeed, female partners of patients with PE are more likely to suffer from sexual problems and dissatisfaction than partners of non-PE men (Byers & Grenier, 2003;Hartmann et al, 2005;Hobbs et al, 2008;Graziottin & Althof, 2011;Limoncin et al, 2013). Interestingly, a previous study evaluating the associations between intimacy, quality of life, and sexual dysfunction in men, demonstrated that all aspects of intimacy were lower in men reporting PE than in men not reporting PE (McCabe, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It shows the increasing tendency to diagnose a sexual problem as a disorder only when it causes personal distress rather than interpersonal difficulties. Another important reason for emphasizing personal distress might be that some individuals suffering from sexual disorders do not have partners and therefore partner distress or interpersonal difficulties may not be universally applicable to all people (14,15).…”
Section: A Comparison Of Dsm IV Tr and Proposed Dsm 5 Classificationsmentioning
confidence: 99%